Post-quantum Simpson's type inequalities for coordinated convex functions - Xue-Xiao You; Muhammad Aamir Ali; Ghulam Murtaza; Saowaluck Chasreechai; Sotiris K. Ntouyas; Thanin Sitthiwirattham (AIMS Mathematics, 2022)
In this paper, we prove some new Simpson's type inequalities for partial (p,q)-differentiable convex functions of two variables in the context of (p,q)-calculus. We also show that the findings in this paper are generalizations of comparable findings in the literature.